Video Persuasif Sebagai Upaya Peningkatan Jumlah Pembayaran Pajak Kendaraan Bermotor Di Kabupaten Lombok Tengah - Martina Fariza; Wire Bagye (FKIP, Universitas Palangka Raya, 2024)
Rapid advances in technology, especially through online and offline media, have changed the way people connect, access information and share views. YouTube has become the main platform for users to interact and distribute multimedia content, one of the contents of which is persuasive videos. Persuasive videos influence and convey messages to the public, such as raising awareness about the obligation to pay motor vehicle tax. The method used is the Multimedia Development Life Cycle (MDLC) method in making persuasive videos. MDLC stages include concept, design, material collection, assembly, testing, and distribution. The video was produced with a focus on motor vehicle tax payment guidelines, with a duration of 2 minutes 12 seconds. Evaluation carried out through a survey of STMIK Lombok students and verification by SAMSAT employees, shows that this video is effective in conveying information and increasing public understanding about the importance of paying motor vehicle tax. Respondents prefer presenting content via video rather than photos or writing.